Enhancing the Usability of ITG Virtual Tour Website Through UI/UX Design Using the Five Planes Method - Ridwan Setiawan; Muhamad Faturrahman; Yosep Septiana; Dewi Tresnawati; Ade Sutedi (Center for Research and Community Service, Institut Informatika Indonesia (IKADO) Surabaya, 2025)
The virtual tour website in higher education significantly enhances campus information accessibility; yet, the poor usability of the ITG Virtual Tour website leads to a subpar user experience. This research offers a redesign of the UI/UX utilizing the Five Planes technique, which prioritizes clarity in information and navigation. A System Usability Scale (SUS) was employed to evaluate the site's usability prior to and after the redesign, adhering to the five stages of The Five Planes: Strategy, Scope, Structure, Skeleton, and Surface. The test findings indicated that the initial SUS score of 51.17 (classified as